Android-based Family Counseling Training for Parents of Children with Cerebral Palsy - Nurhastuti Nurhastuti; Tasha Dwilamiisa Putri; Jehan Nabela Oktaviani (JETL (Journal of Education, Teaching and Learning), 2025)
Parents' behavioral disorders toward children with cerebral palsy are caused by the wrong perception and the lack of knowledge about cerebral palsy. The initial process of caring for children with cerebral palsy is empowering. Empowering is given to the parents through counseling to help parents accept their children's condition and implant a positive attitude toward their children. Family counseling provides knowledge and skills for parents with cerebral palsy. The counseling is conducted through an android-based application that can be easily accessed by parents to receive knowledge on how to nurture children with cerebral palsy. Thus, this research aims (1) to give knowledge and teach skills on raising children with cerebral palsy using an android-based application, (2) to motivate parents, and (3) to provide guidance and counseling to solve parenting problems. Analysis was conducted using Wilcoxon signed rank technique to identify the differences between pretest and posttest. The test resulted in a Zscore of -3.417 with Asymp. Sig. (2-tailed) 0,001. The probability value is α = 0,05, thus the probability of Zscore is less than the predetermined probability (0,001 < 0,05). Findings of the research showed that android-based training in family counseling has influenced the understanding and skills of parents of children with cerebral palsy in Payakumbuh